The Bigger the Better? Center Volume Dependent Effects on Procedural and Functional Outcome in Established Endovascular Stroke Centers - Hahn, Marianne; Gröschel, Sonja; Tanyildizi, Yasemin; Brockmann, Marc A.; Gröschel, Klaus; Uphaus, Timo, German Stroke Registry-Endovascular Treatment (GSR-ET) Investigators; Reich, A; Nikoubashman, O; Röther, J; Eckert, B; Braun, M; et al. (Frontiers in Neurology, 2022)
Background: Mechanical thrombectomy (MT) rates for the treatment of acute ischemic stroke due to large vessel occlusion are steadily increasing, but are delivered in heterogenic settings. We aim to investigate effects of procedural load in centres with established MT-structures by comparing high vs. low volume centres with regard to procedural characteristics and functional outcomes. Methods: Data from 5379 patients enrolled in the German Stroke Registry Endovascular Treatment (GSR-ET) between June 2015 and December 2019 were compared between three groups: high volume: ≥180 MTs/year, 2342 patients; medium volume: 135-179 MTs/year, 2202 patients; low volume: <135/MTs/year, 835 patients. Univariate analysis and multiple linear and logistic regression analyses were performed to identify differences between high vs. low volume centres. Results: We identified high vs. low volume centres to be an independent predictor of shorter intra-hospital (admission to groin puncture: 60min vs. 82min, β=-26.458; p<0.001) and procedural times (groin puncture to flow restoration: 36min vs. 46.5min; β=-12.452; p<0.001) after adjusting for clinically relevant factors. Moreover, high volume centres predicted a shorter duration of hospital stay (8d vs. 9d; β=-2.901; p<0.001) and favourable medical facility at discharge (transfer to neurorehabilitation facility/home vs. hospital/nursing home/in-house fatality, OR 1.340, p= 0.002). Differences for functional outcome at 90 day follow-up were observed only on univariate level in the subgroup of primarily to MT centre admitted patients (mRS 0-2 38.5% vs. 32.8%, p=0.028), but did not persist in multivariate analyses. Conclusion: Differences in efficiency measured by procedural times call for analysis and optimization of in-house procedural workflows at regularly used but comparatively low procedural volume MT centres. Trial Registration: Registration-URL: http://www.clinicaltrials.gov; Unique identifier: NCT03356392.